Pengaruh Total Aset, Tingkat Solvabilitas, dan Opini Audit Pada Audit Delay - Aryaningsih, Ni Nengah Devi; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 7 No 3 (2014), 2014)
ABSTRACT Audit Delay is the time span of completion of the audit conducted by auditors in carrying out the field work. Auditing process requires a lot of time because it requires precision in auditing financial statements that indicate the length of the Audit Delay . The purpose of this study was to determine the effect of the total assets of the company, the level of solvency as well as the auditor's opinion on Audit Delay . The population in this study is a manufacturing company that is listed on the Indonesia Stock Exchange 2009-2011. The number of samples obtained as many as 144 companies that have been determined by purposive sampling method. The data analysis technique use dismultiple linear regression analysis. The test results showed that thevariabels affect the solvency and the auditor's opinion on Audit Delay , where as no effect on total asets   Audit Delay .     Keywords : total asets , solvency , the auditor's opinion , the Audit Delay
Keywords: total assets< solvency, the auditor' s opinion, the audit delay